Assessing immigrant entrepreneur’s contribution to entrepreneurial development: A case of small retailers in the Mangaung, Free State province - Lebohang Y. Moloi; Lentswe Mosweunyane; Crispen Chipunza (The Southern African Journal of Entrepreneurship and Small Business Management, 2022)
Background: Despite numerous training programmes by the South African (SA) government equipping citizens with entrepreneurial skills to create businesses for economic development. The country still faces a high rate of liquidation of businesses leading to unemployment.